2018
DOI: 10.1002/ajpa.23448
|View full text |Cite
|
Sign up to set email alerts
|

Neck function in early hominins and suspensory primates: Insights from the uncinate process

Abstract: Suspensory primates exhibit the most pronounced uncinates, likely to maintain visual field stabilization. East African hominins exhibit reduced uncinate processes compared with African apes and A. sediba, likely signaling different degrees of neck motility and modes of locomotion. Although soft tissues constrain neck flexibility beyond limits suggested by osteology alone, this study may assist in modeling cervical kinematics and positional behaviors in extinct taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 157 publications
(193 reference statements)
1
6
0
Order By: Relevance
“…For example, the neck can stabilize the head when the trunk moves during locomotion, and it can also move the head on a stationary trunk to locate the source of an external stimulus. Correlations between cervical vertebral morphology and positional behavior (i.e., neck posture and/or locomotor mode) across primates have been detected in previous work (Manfreda, Mitteroecker, Bookstein, & Schaefer, ; Meyer, Woodward, Tims, & Bastir, ; Nalley, ; Nalley & Grider‐Potter, , ). These studies have focused their interpretations of cervical variation within the context of locomotor differences but have yet to test these inferences directly.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…For example, the neck can stabilize the head when the trunk moves during locomotion, and it can also move the head on a stationary trunk to locate the source of an external stimulus. Correlations between cervical vertebral morphology and positional behavior (i.e., neck posture and/or locomotor mode) across primates have been detected in previous work (Manfreda, Mitteroecker, Bookstein, & Schaefer, ; Meyer, Woodward, Tims, & Bastir, ; Nalley, ; Nalley & Grider‐Potter, , ). These studies have focused their interpretations of cervical variation within the context of locomotor differences but have yet to test these inferences directly.…”
Section: Introductionsupporting
confidence: 68%
“…Although they are thought to provide joint stability, it could be that soft tissue more strongly inhibits motion. Meyer et al () published a geometric morphometric analysis of uncinate process morphology in primates. The results indicated that larger primates tend to have relatively shorter processes than do smaller bodied species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had been conducted to measure parameters of the spine in mammals, and the anatomy of the baboon has been directly used to compare with the related structures in human subjects [19]. Some comparative anatomical analyses of cervical vertebrae between human subjects and nonhuman primates have also been conducted [20][21][22][23][24]. For example, Manfreda et al [24] used geometric morphometry to study the relationship between the morphology of the atlas and the movement pattern of primates and indicated that the human atlas morphology may be a unique adaption.…”
Section: Introductionmentioning
confidence: 99%
“…Nalley et al [21] assessed the morphology of the upper cervical vertebrae of primates and identified a significant association between the head and neck posture and the morphology of the cervical spine. Meyer et al [23] evaluated the uncinate processes of existing primates to construct a cervical kinematics model of Anatomy early fossil hominins. Nakatsukasa et al [22] demonstrated that the bipedal movement of macaques after training is inconsistent with that of human subjects, which may be the result of a genetic limitation.…”
Section: Introductionmentioning
confidence: 99%